PREDIKSI KUNJUNGAN PASIEN RAWAT JALAN TAHUN 2018 – 2020 DI RSUD KOTA BANDUNG - Irda Sari S.ST (Jurnal Akrab Juara, 2019)
The increase in the human population has an increasing impact on public awareness about health. One of them is an increase in the number of outpatient patient visits in Bandung City Hospital. This study aims to determine the predictions of outpatient visits in 2018-2020 in Bandung City Hospital. This research method is descriptive research, using interviews, observation, and bibliography. Data was obtained from the daily outpatient census recapitulation in 2015-2017. The results of the predictions in 2018-2020, the number of patients visiting internal medicine, neurology, physiotherapy, children's, eye and heart health had increased by 8.5% annually.So that the hospital must add capacity to existing facilities and improve the quality of services provided. This is so that the patient's handling process can run quickly and the patient can be well served.